The water frogs’ (Pelophylax esculentus complex) intrapopulation ontogenetic strategies - Усова, О. Є.; Кравченко, М. О.; Шабанов, Д. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
575 representatives of Pelophylax esculentus complex (193 P. ridibundus, 348 diploid and 34 triploid P. esculentus) from Kharkivska oblast have been studied using skeletochronology. With approximation by the LS method, frogs’ diversity on age and body length has been characterized by two regression lines, which correspond to relatively smaller and bigger individuals of the same age. We compared these individuals by population-biological parameters and registered syndromes (complexes of related traits), allowing their consideration as manifeatation of intrapopulation ontogenetic strategies (IOS). IOS of undersized/oversized is characterized by relatively low/high growth rate, high/low life expectancy, low/high fertility of females and relatively large/small number of breeding seasons in which the individual takes part. Participation in spawning begins early/late in undersized/oversized females and vice versa in males. By using simulation it has been shown that differences in IOS between P. ridibundus and P. esculentus can provide their sustainable coexistence in the hemiclonal population system.